State-of-the-Art Review of Bibliographic Control of Higher Education in Canada - Wilburn, Marion T.; Knapper, Christopher K. (Canadian Journal of Higher Education, 1982)
During the last two decades the quantity and variety of materials providing information on higher education in Canada have increased greatly. Nevertheless, researchers, administrators, instructors and students find it difficult to identify and locate relevant items. The following article reports on a survey of Canadian agencies and institutions collecting higher education materials; identifies four problem areas - definitions, collection policies, accessibility, and collection co- ordination; and recommends further information exchange and the compilation of a more complete directory of collections in higher education.